Analisis Framing pada Pemberitaan AI dan Koding dalam Kurikulum Pendidikan di CNN Indonesia dan Tempo.co - Rosada, Anisa Amrina; Adiprabowo, Vani Dias (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze how CNN Indonesia and Tempo.co frame the issue of AI and coding in the Indonesian education curriculum. This study uses a qualitative content analysis method with the framing model of Zhongdang Pan and Gerald M. Kosicki. The research data consists of news articles from CNN Indonesia and Tempo.co discussing the integration of AI and coding in the national curriculum. Data selection was carried out using purposive sampling. Analysis was conducted using four framing structures: syntactic, script, thematic, and rhetorical. The results show that both media construct ambivalent framings towards AI in education. CNN Indonesia tends to highlight AI as an educational innovation that can improve the quality of learning and student creativity. Meanwhile, Tempo.co focuses more on social and moral challenges, such as the changing role of teachers and the impact of AI on the learning process. The conclusion of this study shows that media framing plays a significant role in shaping public understanding and the direction of AI-based education policy in Indonesia. Keywords: Artificial Intelligence, Education, Framing Analysis, Online Media, Media Discourse.